Reactive oxygen species generation and peroxidase activity during Oidium neolycopersici infection on Lycopersicon species - Mlícková, Katerina; Luhová, Lenka; Lebeda, Ales; Mieslerová, Barbora; Pec, Pavel (Plant physiology and biochemistry, 2004)
Histochemical and biochemical study of plant tissue responses were carried out on three Lycopersicon spp. accessions differing in response to Oidium neolycopersici. High production of superoxide anion was observed mainly in infected leaves of highly susceptible Lycopersicon esculentum cv. 'Amateur' during the first hours post inoculation (hpi). The production of hydrogen peroxide as well as an increase of peroxidase (POX) activity were detected mainly in resistant accessions at 4-12 hpi. A signal confirming the presence of very active POX was found in the apical part of tubes of germinating fungus and inside dead conidia. Increased soluble POX and catalase activity in leaf extracts of resistant accessions L. chmielewskii (LA 2663) and L. hirsutum (LA 2128) (20 hpi) correlated with the percentage of dead cells in infection sites. The correlation between production of reactive oxygen species (ROS) and activity of enzymes participating in their metabolism and hypersensitive response was evident during plant defence response.
Keywords: Solanum lycopersicum; Ascomycota; reaktivní formy kyslíku; Peroxidases; peroxidasy; Reactive Oxygen Species